Behavioral Cooperation or Conflict of Human Intestinal Roundworms and Microbiomes: A Bio-Activity Perspective - Meisam Khazaei; Malihe Parsasefat; Aisa Bahar; Hamed Tahmasebi; Valentyn Oksenych (Cells)
Human infections are greatly impacted by intestinal nematodes. These nematodes, which encompass the large roundworms, have a direct impact on human health and well-being due to their close cohabitation with the host’s microorganisms. When nematodes infect a host, the microbiome composition changes, and this can impact the host’s ability to control the parasites. We aimed to find out if the small intestinal roundworms produce substances that have antimicrobial properties and respond to their microbial environment, and if the immune and regulatory reactions to nematodes are altered in humans lacking gut microbes. There is no doubt that different nematodes living in the intestines can alter the balance of intestinal bacteria. Nonetheless, our knowledge about the parasite’s influence on the gut microbiome remains restricted. The last two decades of study have revealed that the type of iron utilized can influence the activation of unique virulence factors. However, some roundworm proteins like P43, which makes up a large portion of the worm’s excretory-secretory product, have an unknown role. This review explores how the bacterial iron regulatory network contributes to the adaptability of this opportunistic pathogen, allowing it to successfully infect nematodes in different host environments.